How food regulators communicate with consumers about food safety. Issue 8 (3rd August 2015) - Wilson, Annabelle M; Meyer, Samantha B; Webb, Trevor; Henderson, Julie; Coveney, John; McCullum, Dean; Ward, Paul R.
Abstract : Purpose: – The purpose of this paper is to report how food regulators communicate with consumers about food safety and how they believe consumers understand their role in relation to food safety. The implications of this on the role of food regulators are considered. Design/methodology/approach: – In total, 42 food regulators from Australia, New Zealand and the UK participated in a semi-structured interview about their response to food incidents and issues of food regulation more generally. Data were analysed thematically. Findings: – Food regulators have a key role in communicating information to consumers about food safety and food incidents. This is done in two main ways: proactive and reactive communication. The majority of regulators said that consumers do not have a good understanding of what food regulation involves and there were varied views on whether or not this is important. Practical implications: – Both reactive and proactive communication with consumers are important, however there are clear benefits in food regulators communicating proactively with consumers, including a greater understanding of the regulators' role. Regulators should be supported to communicate proactively where possible. Originality/value: – There is a lack of information about how food regulators communicate with consumers about food safety and how food regulators perceive consumers to understand food regulation. It is this gap that forms the basis of this paper.